The Lord’s Supper — Gift and Gratitude: A Baptist’s View - Swarat, Uwe (Journal of European Baptist Studies, 2023)
Baptist theology, at least in German-speaking countries, has usually paid little attention to the Lord’s Supper. Nevertheless, the Lord’s Supper plays such an important role in Holy Scripture, in church traditions, in the ecumenical dialogues of the twentieth century, and in the reality of church life, that it seems unreasonable to neglect it theologically. So, this article seeks to stimulate Baptist thinking on the Lord’s Supper in the light of tradition and Scripture. The author argues that Baptists have too often sought to link themselves to Zwingli instead of Calvin. That means they have too often adopted a purely symbolic, anti-sacramental understanding of the Lord’s Supper. But this understanding does not correspond to the biblical accounts of its institution. In contrast, Calvin’s teaching on the Lord’s Supper understands the Supper as a work of grace and of faith in one. This twofold meaning is clearly expounded in the Consensus Tigurinus of 1549 and is of great ecumenical significance today.